Not teaching, but coaching creating a self-development culture in a classroom - GROCHALSKA, MONIKA (Journal of Education Culture and Society, 2020)
Nowadays we hear a lot about coaching, but what does coaching really mean? Why does it matter? What is more, the notion of edu-coaching has also emerged in recent years, and this idea seems to be gaining popularity. But can coaching replace traditional classro-om education? To what extent could it be useful at school?In the first part of this article I would like to define what coaching is, how it is different from mentoring and how it can be used to support pupils and teachers at personal, team and whole school levels. Undoubtedly, there are obvious benefits of coaching for students, staff, school as well as coaches.There are three core skills of coaching: listening, questioning and reviewing. To be a good coach, a teacher should understand how to be a good listener and how to ask proper coaching questions. They should ask questions that help them and the coached/the pupil to review, reflect and to clarify matters throughout the lesson. There are some coaching tools that can be used at various stages of the coaching process at school, including the balance wheel, rating scale, bisociation, viewpoints and motiva-tional record. A teacher can successfully use coaching on the basis of the GROW (Goal, Reality, Options and Will) model. It can support the teacher’s development and his practice as a coach. As indicated in the on-line articles for teachers, starting professional training is also worthwhile. During the training, a teacher can learn how to develop classroom practice that supports growth through the use of high level listening, questioning, reflecting and summarising. Most of professional training programs contain the following elements:• using active listening and open questions to tackle issues such as pupil behaviour, • reaching their full potential by putting in place realistic goals and plans to achievethem,• taking responsibility for their own progress through change,• building rapports that can turn previously difficult interactions into productive ones.Such skills allow the teachers to create a self-development culture in their classrooms.I would like to ponder upon whether these theses have substantive grounds or perhaps they are just empty slogans. Can a teacher also be a good coach? Is it worthwhile to im-plement coaching in the education system? How can coaching help to improve classroom management? These and some other issues will be considered in the following text.